Activist disciplines: Universities in autocracies and political protest - Nils B Weidmann; Mina Rulis (Research & Politics)
Recent events on university campuses show again that academic institutions often constitute breeding grounds for political mobilization. This also applies to autocratic countries, where political protest has been found to be more likely to occur in university cities. However, research so far has failed to address the question of which universities are more likely to see protest. In this paper, we focus on the disciplinary composition of universities in autocracies. We argue that non-STEM disciplines traditionally attract more progressive students, cover more politically sensitive topics, and oftentimes study the determinants of successful mobilization. Therefore, they should be more likely to serve as focal points for political protest. We test our expectations in a large-scale comparative analysis, using fine-grained data on the composition and location of academic institutions in autocracies combined with event data on political protest. We find that political activism is more likely in cities with institutions focused on arts and humanities, which points to the potentially transformative role of these disciplines even in severely constrained political settings.